The power of outliers (and why researchers should ALWAYS check for them) - Osborne, Jason W; Overbay, Amy (Practical assessment, research & evaluation, 2004)
There has been much debate in the literature regarding what to do with extreme or influential data points. The goal of this paper is to summarize the various potential causes of extreme scores in a data set (e.g., data recording or entry errors, motivated mis-reporting, sampling errors, and legitimate sampling), how to detect them, and whether they should be removed or not. Another goal of this paper was to explore how significantly a small proportion of outliers can affect even simple analyses. The examples show a strong beneficial effect of removal of extreme scores. Accuracy tended to increase significantly and substantially, and errors of inference tended to drop significantly and substantially once extreme scores were removed.